2023
DOI: 10.1038/s41467-022-35739-8
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing cholecystokinin A receptor in the lung attenuates obesity-induced airway hyperresponsiveness

Abstract: Obesity increases asthma prevalence and severity. However, the underlying mechanisms are poorly understood, and consequently, therapeutic options for asthma patients with obesity remain limited. Here we report that cholecystokinin—a metabolic hormone best known for its role in signaling satiation and fat metabolism—is increased in the lungs of obese mice and that pharmacological blockade of cholecystokinin A receptor signaling reduces obesity-associated airway hyperresponsiveness. Activation of cholecystokinin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The most significant DEG in the silico TWAS of atopic asthma that was previously found using observed expression was CCK (cholecystokinin), which has been linked to airflow limitation in obesity-related asthma 34 . Other genes included CTSC (which influences cell-mediated immune responses and immune cell trafficking in the airways) 35 and other genes previously discussed.…”
Section: Resultsmentioning
confidence: 96%
“…The most significant DEG in the silico TWAS of atopic asthma that was previously found using observed expression was CCK (cholecystokinin), which has been linked to airflow limitation in obesity-related asthma 34 . Other genes included CTSC (which influences cell-mediated immune responses and immune cell trafficking in the airways) 35 and other genes previously discussed.…”
Section: Resultsmentioning
confidence: 96%
“…FFAs have the capacity to induce mitochondrial ROS, potentially contributing to inflammation and endothelial dysfunction [ 38 ]. Notably, in an HFD-induced obesity model, one study revealed an autocrine stimulatory loop involving CCK-activated, CCKA receptor-mediated airway smooth muscle contraction, a process potentially exacerbated by elevated FFAs [ 11 ]. Our observations in HFD mice indicated the increases of both FFAs and CCK in the serum and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in obese mice, elevated free fatty acid (FFA) levels stimulate cholecystokinin (CCK) secretion, potentially contributing to AHR via enhanced CCK receptor expression in lung smooth muscles. Blocking CCK receptors has shown promise in mitigating AHR in asthma with obesity patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung CCK level is significantly increased in obese mice and CCK-1 receptor antagonists suppress the innate AHR to methacholine in obese animals [218] Substance P Animal Study NK1 receptor expression is increased on lung epithelium and adipose tissue in murine obese-asthma model [229] Animal Study…”
Section: Review Articlementioning
confidence: 99%
“…Furthermore, mice with a high-fat diet or genetically induced obesity were characterized by an increased level of CCK in the lungs and the administration of the CCK-1 antagonists suppressed the innate airway hyperresponsiveness to methacholine in obese animals. These results suggest that blocking of CCK receptors may have a beneficial effect in the case of co-occurring asthma and obesity [ 218 ].…”
Section: Peptides In Asthma–obesity Phenotypementioning
confidence: 99%